In situ monitoring of pharmaceutical crystallisation - Aina, Adeyinka Temitope (2012)
Using confocal Raman spectroscopy/microscopy, we have monitored pharmaceutical crystallisation 'in situ' in three model (well characterised polymorphic systems) Active Pharmaceutical Ingredients (APIs) and one previously unstudied system where polymorphism had not being reported prior to this study: flufenamic acid, a Non Steroidal Non-Inflammatory Drug (NSAID); nifedipine, an antihypertensive; tolbutamide, used in the treatment of type II diabetes; and imipramine hydrochloride, an antidepressant respectively. Constrained crystallisation from the solid amorphous state was utilised to kinetically trap polymorphs via the Ostwald's rule of stages. Particular emphasis was placed on the phonon-mode/low wavenumber region (4-400cm-1) of the Raman spectral window (this region provides useful information about lattice environment). In all cases our results from the Raman experiments were complemented with similar experiments using Differential Scanning Calorimetry (DSC) and Variable Temperature X-ray Powder Diffraction (VTXRPD). To reduce data complexity, principal component analysis was deployed and found to be extremely effective. In chapter two, a multi-technique study of flufenamic acid (FFA) was carried out which served as a groundwork for later chapters. A solid-solid transformation between two forms of FFA (forms I and III) was observed, due to the abrupt nature of this transition, the 'Lindemann vibrational catastrophe' was envisaged as a possible mechanism for the transformation. Using FFA as a test case in chapter three, polymorphic transformations was monitored in both FFA forms I and III using in situ Raman spectroscopy (as well as VTXRPD) by adopting the constrained crystallisation approach. The approach showed excellent promise (with the XRPD patterns of FFA form II and one unknown form uncovered) and was further explored in later chapters using a variety of pharmaceutical materials. While in chapter four, the interconversion between the different polymorphs of nifedipine was studied using the constrained crystallisation approach monitored using in situ Raman spectroscopy (together with VTXRPD and DSC), our results compared favourably well with those previously published in literature. We also reported for the first time the phonon-mode Raman spectral for this system as earlier publications focussed only on the 'traditional' fingerprint region. Similarly in chapter five, in situ Raman spectroscopy was also used to monitor the polymorphic transformations in tolbutamide (using the constrained crystallisation approach), results from the Raman analysis was compared with those obtained from VTXRPD and found to be in agreement. Thus further showing that Raman spectroscopy combined with the constrained crystallisation approach is a veritable tool for monitoring polymorphic transitions. In chapter six, preliminary results (Raman/XRPD/DSC) showed for the first time that imipramine hydrochloride exhibits polymorphism, with the possibility of at least two new polymorphs. Combination of state of the art spectroscopic techniques with appropriate statistical methods, X-ray powder diffraction and DSC was shown to be an extremely effective approach to investigating and characterising polymorphism in drugs, often using only milligram or sub-milligram sample quantities. Lastly in chapter seven, the novel technique of Transmission Raman Spectroscopy (TRS) was employed in carrying out a quantitative study of polymorphic content in a model pharmaceutical formulation and the results obtained compared with those from traditional backscattering geometry. The transmission method is shown to provide a true bulk measurement of the composition, being unaffected by systematic or stochastic sub-sampling issues that can plague traditional backscattering geometries.